Volatility implications for asset returns correlation - Illia Ivanov (Central European Economic Journal (CEEJ), 2024)
Although there is an extensive literature on the impact of volatility on asset returns correlation, investigating this in relation to broad asset selection and in perspective of different timelines has received less attention. In comparison to the previous papers, we use a much broader set of 35 selected asset classes and used rolling returns for five different periods ranging from 3 months to 5 years to calculate rolling correlations, which was used further for regression analysis between rolling correlation and volatility index (VIX). Results showed more impact of volatility on the midterm horizon, such as 1 year, possibly meaning that for longer periods, structural economic factors impact correlation significantly, while for shorter periods, immediate market reactions to events and short-term fluctuations reduce the impact of the correlation. Autocorrelation of residuals suggests that correlation follows trends, which is evidenced more in longer periods. The study contributes to existing literature by comparing the volatility impact across a broad range of assets and multiple time horizons, revealing that correlation is sensitive to time horizons - overall and in terms of responses to heightened volatility. Also, the impact of volatility is different over different time periods, with most impact for the mid-time horizon, such as 1 year.
Keywords: G11; G12; G14; 330; Asset correlation; volatility; market stress; diversification; portfolio management